PELATIHAN KOMUNIKASI PEMASARAN DAN TEKNIK PENJUALAN PRODUK KREATIF DI DESA BATURITI KERAMBITAN, KABUPATEN TABANAN - Surata, I Ketut; Hanugerah Kristiono Liestiandre; Irene Hanna H. Sihombing; I Putu Utama; Ida Ayu Putri Widawati; Titien Damayanti; Ni Made Eka Mahadewi7; I Wayan Sukma Winarya Prabawa (Jurnal Pengabdian Kepada Masyarakat Makardhi, 2024)
Baturiti Village, located in the Kerambitan District, Tabanan Regency, is known as the cultural tourism destination "Kokokan" and a center for agriculture. The village has an administrative structure consisting of six Banjar Dinas (community organizations) and two Desa Adat (customary villages). The development of tourism in this village, marked by the presence of the Pokdarwis Baturiti Berseri tourism awareness group, demands an improvement in the skills and professionalism of the community in tourism marketing, destination management, and entrepreneurship. Training in these areas is planned as an effort to enhance services to tourists. The training concept includes marketing aspects and the marketing process, as well as various definitions from experts. Furthermore, the marketing concept aimed at meeting the needs and desires of the target market serves as the foundation for carrying out marketing activities. There are six basic marketing concepts underlying the implementation of marketing activities, such as production concept, product concept, selling concept, marketing concept, social marketing concept, and global marketing concept. The marketing process is explained through steps such as understanding the market, designing customer-oriented marketing strategies, preparing integrated marketing plans and programs, building relationships with customers, and deriving value from customers. Training and the application of these marketing concepts are expected to enhance the performance of tourism and the economy in Baturiti Village.